2021
DOI: 10.1016/j.jtumed.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the use of preprints to accommodate the ‘quality’ factor in response to COVID-19

Abstract: Preprints are typically crude precursors of peer-reviewed papers that are placed almost immediately, save for some superficial screening, on an open-access repository to allow the information to reach readers quickly, circumventing the long-drawn process typically associated with processing in peer-reviewed journals. For early-career researchers who might be enthusiastic about obtaining some recognition for their efforts, or wanting open and public input about their work, preprints are certainly a useful publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Although preprints have been established in some disciplines for more than 20 years, the COVID-19 pandemic has revealed the rapid progress of preprints, both for their value and their shortcomings. (8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Preprints are considered to lack scientific integrity, credibility and quality, and there is still reservation among editors, publishers, journals and researchers about the role of preprints and their contribution to science. (6,30,(35)(36)(37)(38)(39) The evidence provided several process issues related to why preprints lack quality, screening, or quality checks during the submission of a manuscript to a preprint server.…”
Section: Barriers and Challenges Associated With Preprintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although preprints have been established in some disciplines for more than 20 years, the COVID-19 pandemic has revealed the rapid progress of preprints, both for their value and their shortcomings. (8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Preprints are considered to lack scientific integrity, credibility and quality, and there is still reservation among editors, publishers, journals and researchers about the role of preprints and their contribution to science. (6,30,(35)(36)(37)(38)(39) The evidence provided several process issues related to why preprints lack quality, screening, or quality checks during the submission of a manuscript to a preprint server.…”
Section: Barriers and Challenges Associated With Preprintsmentioning
confidence: 99%
“…(8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) Preprints are considered to lack scientific integrity, credibility and quality, and there is still reservation among editors, publishers, journals and researchers about the role of preprints and their contribution to science. (6,30,(35)(36)(37)(38)(39) The evidence provided several process issues related to why preprints lack quality, screening, or quality checks during the submission of a manuscript to a preprint server. (28,40,41) It was reported that only three preprint servers (Research Square, bioRxiv and medRxiv) check if the content contains unfounded medical claims.…”
Section: Barriers and Challenges Associated With Preprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preprints were common in arXiv server populated by physics, mathematics, computer science, but COVID-19 pandemic has sped up the rate at which scholars from other disciplines deposit their contents into other servers before review process takes place(Majumder & Mandl, 2020). This is true despite preprints are regarded as the crude precursors of peer-reviewed papers , they need proper scrutiny and assurance of stringent adherence to ethical policies prior to releasing them to audience for public consumption (Teixeira da Silva, 2021). Careful scrutiny of the high increase of preprints in the domain of biomedicine, COVID-19 pandemic has consolidated the rise of using these information resources to better understand the pattern of progressing of the virus and need to develop a vaccine (Majumder & Mandl, 2020).…”
Section: Preprints and Its Evolutionmentioning
confidence: 99%
“…Moreover, a lesser known concern is the preprint publication of false research that has increased since the COVID-19 pandemic. 7 Preprints are typically unrefined pre-publications of peer-reviewed papers that are placed almost immediately after some superficial screening. This allows information to reach readers quickly while bypassing the long-drawn process required in officially publishing through peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%